The South China Sea dispute : navigating diplomatic and strategic tensions - Storey, Ian, 1970-; Lin, Zhengyi, 1956- (Singapore : ISEAS Yusof Ishak Institute, 2016)
Increasing tensions in the South China Sea have propelled the dispute to the top of the Asia-Pacific's security agenda. Fuelled by rising nationalism over ownership of disputed atolls, growing competition over natural resources, strident assertions of their maritime rights by China and the Southeast Asian claimants, the rapid modernization of regional armed forces and worsening geopolitical rivalries among the Great Powers, the South China Sea will remain an area of diplomatic wrangling and potential conflict for the foreseeable future. Featuring some of the world's leading experts on Asian security, this volume explores the central drivers of the dispute and examines the positions and policies of the main actors, including China, Taiwan, the Southeast Asian claimants, America and Japan. The South China Sea Dispute: Navigating Diplomatic and Strategic Tensions provides readers with the key to understanding how this most complex and contentious dispute is shaping the regional security environment.
Untangling a complex web, understanding competing maritime claims in the South China Sea / Clive Schofield -- China debates the South China Sea dispute / Mingjiang Li -- Taiwan's evolving policy towards the South China Sea dispute, 1992-2016 / Anne Hsiu-an Hsiao and Cheng-yi Lin -- The South China Sea, primary contradictions in China-Southeast Asia relations / Alice D. Ba -- Rising tensions in the South China Sea, Southeast Asian responses / Ian Storey -- The Philippines and the South China Sea dispute, security interests and perspectives / Aileen S.P. Baviera -- A Vietnamese perspective on the South China Sea dispute / Hoang Anh Tuan -- The South China Sea dispute, options for Malaysia / Elina Noor -- The United States and the South China Sea, front line of hegemonic tension? / Denny Roy -- The South China Sea dispute in U.S.-ASEAN relations / Yann-Huei Song -- Japan and the South China Sea dispute, a stakeholder's perspective / Yoichiro Sato.
Title from publisher's bibliographic system (viewed on 05 Jun 2017).
Keywords: Law of the sea -- South China Sea; Dispute resolution (Law) -- Southeast Asia; South China Sea -- International status; South China Sea -- Claims; China -- Foreign relations -- Southeast Asia; Southeast Asia -- Foreign relations -- China